Persuasion Strategy in Sayang Hijab Detergent Advertisement: A Critical Discourse Analysis of Tirta's Role as an Expert Endorser - Luk Luatul Ilmiyyah; Alfian Setya Nugraha (Raja Zulkarnain Education Foundation, 2026)
This study analyzes the persuasive strategies used in the Sayang Hijab version of the Sayang detergent advertisement that uses Dr. Tirta as an expert endorser. This study was conducted to uncover the mechanism of medical authority construction and persuasive strategies used in the Sayang Hijab version of the Sayang detergent advertisement, which involves Dr. Tirta as an expert endorser. This study uses a qualitative descriptive method with the Critical Discourse Analysis (CDA) model from Norman Fairclough’s theory. Norman Fairclough’s CDA theory has three dimensions: text analysis, discourse practice, and sociocultural practice. The results of this study indicate that in the text analysis, Dr. Tirta as an expert endorser in this advertisement uses medical language to create new standards of cleanliness and safety in the advertisement of detergent products. In this discourse practice, there is a synergy of authority between the emotional experience of consumers, as depicted by Ria Ricis & Moana, and the rational validation of medical experts, as depicted by Dr. Tirta. From a sociocultural perspective, this detergent advertisement reflects a shift in public mindset after the pandemic, where there is an increased reliance on expert judgment rather than domestic decisions. This study concludes that the use of laboratory settings and medical attributes is not only about the marketing appeal of an advertisement, but is more an attempt to reposition detergent from a household necessity to a preventive health instrument.